COMPUTATIONAL ANALYSIS OF CONVECTIVE HEAT AND MASS TRANSFER FLOW OF SECOND GRADE FLUID WITH CHEMICAL REACTION - Rao, N. Srinivasa (ShodhKosh: Journal of Visual and Performing Arts, 2023)
In the present paper, we investigate the effect of chemical reaction the heat generating on the unsteady free convection MHD gyrating flow of radiation and chemical reactive second grade discussed. Here, it is assumed that, the confining plate has the ramped wall temperature with ramped surface concentration and isothermal temperature with ramped surface concentration. The non-linear coupled equations governing the flow, heat and mass transfer are solved numerically by Galerkin Finite Element Analysis. In addition to the idioms of skin friction, Nusselt fluid past an unbounded perpendicular plate during absorbent medium have been number as well as Sherwood number are achieved and characterized numerically with tabular format.